Associação entre variabilidade de frequência cardíaca e apneia obstrutiva do sono com nível de gravidade de COVID-19 - Zacarias, Laíla Cândida (2023)
COVID-19 is a systemic and multisymptomatic disease that has had a global impact due to its transmissibility and mortality rate. Despite the worldwide task force targeting the COVID-19 infection, pathophysiological mechanisms, which are increasingly complex, still remain to be clarified. This dissertation is composed of two products, which in common present COVID-19 as a health condition and differ insofar as it proposes the investigation of variables that are associated with the worst severity of this health condition. Thus, the first study of this dissertation sought to investigate OSA as a potential factor for the severity of COVID-19. This is a descriptive observational study carried out in a tertiary hospital in the State of Ceará, Brazil, between April and May 2021. Participants were approached for convenience at the time of pre-hospital discharge. Individuals aged 18 years or older with a clinical diagnosis of COVID-19, confirmed by the RT-PCR test, and who had adequate conditions to perform sleep polygraphy were included. Thus, individuals using oxygen therapy, invasive or non-invasive mechanical ventilation or tracheostomized were not included. Exclusion criteria were the presence of previous pulmonary disease that generated significant obstructive or restrictive disorder, previous neuromuscular disease, or any cause of pulmonary hypoventilation. The recruited participants answered the WHODAS 2.0 in the form of an interview to assess functioning . Clinical data and laboratory and imaging tests for the day the participant had the worst clinical scenario were collected from the medical records. These data allowed the severity classification of COVID-19. The results found showed that the presence of OSA in individuals hospitalized for COVID-19 is associated with greater severity and worse clinical scenario. These individuals also had a longer period of oxygen therapy, had a higher rate of platelets and D-dimer and lower peripheral oxygen saturation. The second study of this dissertation investigated the autonomic function characterizing the heart rate variability (HRV) profile, clinical and laboratory variables in individuals with COVID-19. This is a cross-sectional descriptive quantitative study carried out in two tertiary hospitals in the state of Ceará, Brazil, from May 2021 to January 2022. Participants were approached for convenience in isolation wards intended for the treatment of COVID-19 in the pre-hospital discharge setting. Individuals aged 18 years or older who had a clinical diagnosis of COVID-19 confirmed by the RT-PCR test were included, and were excluded the individuals using invasive or non-invasive mechanical ventilation, using beta-blockers, oral or inhaled beta agonists and vasoactive drugs, or with a history of syncope, pre-syncope, or known arrhythmias. The recruited participants answered the WHODAS 2.0 in the form of an interview to assess functioning. Clinical data and laboratory and imaging tests on the day the participant had the worst clinical scenario were collected from the medical records, that allowed classifying the severity of COVID-19. Electrocardiographic recordings were performed using a cardiac monitor for a period of 5 minutes of rest in the supine position and 5 minutes after active postural maneuver (APM). The results showed that the HRV parameters in the time domain, the pNN50, and in the frequency domain, the high frequency component – (HF) and the low frequency component (LF) after active postural maneuver, decreased as the COVID-19 severity classification increased, showing impaired autonomic modulation in individuals hospitalized for COVID-19. In addition, they had increased neutrophil counts, decreased lymphocytes, higher systolic blood pressure, respiratory rate, and lower peripheral oxygen saturation. A weak correlation was found between pNN50 and neutrophils, leukocytes, CRP and D-Dimer, and no correlation between lymphocytes. The results found in this dissertation may be useful to clarify the pathophysiological mechanisms of COVID-19, and, therefore, to establish early therapies that positively impact the clinical course, resulting in a favorable prognosis and reducing long-term injuries.